Analisis Kemampuan Pemecahan Masalah Matematis pada Materi Sistem Persamaan Linier Dua Variabel (SPLDV) Ditinjau dari Self Directed Learning - Fadzillah Agustina Lubis; Nur Azizah; Vebiola Ardiani; Cut Latifah Zahari (Jurnal Dirosah Islamiyah, 2023)
This study aims to analyze the mathematical problem solving abilities of class X TKJ-3 SMKN 1 Perbaungan in the material system of two-variable linear equations (spldv) in terms of high, medium and low levels of Self Directed Learning. This research is a qualitative descriptive study. The subjects of this study were students of class X TKJ-3 SMKN 1 Perbaungan. The object of research on the analysis of mathematical problem solving abilities in the matter of a system of two-variable linear equations (spldv) in terms of self-directed learning at SMKN 1 Perbaungan. This study used a test on SPLDV material consisting of 3 essay questions. Analysis of the data that has been carried out the results of this study indicate that: (1) students who have the ability to solve mathematical problems with independent learning levels have been able to overcome the four problem solving indicators according to Polya, namely understanding the problem, planning problem strategies, carrying out calculations, and re-examining. problem solving results. (2) students who have the ability to solve mathematical problems with moderate independent learning levels show that they have been able to fulfill indicators 1 and 3 of problem solving according to Polya, namely understanding problems and carrying out calculations. (3) students who have the ability to solve mathematical problems with low-level independent learning are not able to meet indicators 1, 2, 3, and 4 according to Polya. Keywords: Problem solving ability, two-variable linear equation system, self-directed learning